Conceptions of giftedness and talent (Palgrave Macmillan, 2021)
This book brings together eminent and emerging scholars to present cutting-edge research on diverse conceptions of giftedness and talent from a range of international perspectives. It covers classical views, emphasizing IQ, but also seeks to move the academic debate on from the common exclusive emphasis on IQ-based skills.